Konstruksi Aransemen Bagimu Negeri Melalui Penerapan Ilmu Harmoni dan Kontrapung Dasar - Kaestri, Veronica Yoni; Widodo, Tri Wahyu (PROMUSIKA, 2021)
Artikel ini mengungkapkan proses aktivitas belajar mahasiswa dalam memahami ilmu harmoni dan kontrapung dasar dalam membentuk sebuah aransemen musik. Ilmu harmoni dan kontrapung merupakan ilmu dasar dalam memperlajari penyusunan nada. Dalam proses penyusunan nada terdapat pengetahuan akur, yang terbagi dalam empat suara yaitu sopran, alto, tenor dan bass tersusun secara horisontal. Unsur empat suara memiliki aturan-aturan yang berlaku dalam ilmu harmoni, sedangkan kontrapung dalam proses pembelajaran mempelajari kontrapung instrumental dengan tanganada diatonik dan termasuk dalam musik gaya polifonik. Artikel ini merupakan hasil penelitian proses aplikasi ilmu harmoni dan kontrapung dengan cara mempraktikan membuat aransemen lagu Bagimu Negeri.  Tujuan dari penelitian adalah mengajak mahasiswa dan memahami dalam mengaplikasikan ilmu harmoni dan kontrapung. Melalui cara eksperimen merupakan kegiatan dari proses membuat aransemen lagu Bagimu Negeri dengan pendekatan musikologi. Konstruksi aransemen musik melalui penerapan ilmu harmoni dan kontrapung dengan pendekatan musikologi bermanfaat untuk memberikan pengetahuan pada mahasiswa bagaimana mengaransemen lagu. Hasil akhir penelitian yaitu bagaimana mahasiswa praktik mengaransemen lagu menggunakan ilmu harmoni dan kontrapung yang mengkolaborasi antara ilmu harmoni dan kontrapung. Keterbatasan dalam penelitian ini belum mengungkap kontur dan tekstur harmoni dalam aplikasi aransemen musik. Oleh karena itu memerlukan studi yang lebih jauh kembali dalam memahami aplikasi harmoni dan kontrapung dalam proses aransemen.AbstractThe construction of the music arrangement Bagimu Negeri for the application of harmony and basic counterpunch. This article reveals the learning activity process of students of the S-1 Music Study Program of the Faculty of Performing Arts, Yogyakarta Indonesian Institute of Arts, in understanding the science of harmony and contra punt in forming a musical arrangement. The science of harmony and contra punt is a basic science in learning the preparation of tone. There is knowledge of getting along in composing the tone, divided into four sounds: soprano, alto, tenor, and bass arranged horizontally. Element four sounds have rules that apply in the science of harmony. At the same time, contra punt in the learning process learns instrumental contra punt with diatonic hands and in polyphonic style music. This article results from research in the application process of harmonic and counter punt science by making arrangements for songs for the country.  The study aims to invite students and understand in applying the science of harmony and contra punt. The way of experimentation is to make arrangements of songs for the country with a musical approach. Construction of music arrangements through the application of harmonic science and contra punt with a musicology approach is helpful for students to arrange songs. The final result of the study is how students practice arranging songs using the science of harmony and contra punt that collaborate between the science of harmony and contra punt. Limitations in this study have not revealed the contours and textures of harmony in musical arrangement applications. It, therefore, requires a further analysis back in understanding the application of harmony and contra punt in the arrangement process.Keywords: the science of harmony and contra punt; musical arrangements; Bagimu Negeri; Harmonic texture